2017
DOI: 10.1016/j.brat.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

A non-inferiority trial of Prolonged Exposure for posttraumatic stress disorder: In person versus home-based telehealth

Abstract: This is the first randomized controlled trial to evaluate non-inferiority of Prolonged Exposure (PE) delivered via home-based telehealth (HBT) compared to standard in-person (IP) PE. One-hundred thirty two Veterans recruited from a Southeastern Veterans Affairs Medical Center and affiliated University who met criteria for posttraumatic stress disorder (PTSD) were randomized to receive PE via HBT or PE via IP. Results indicated that PE-HBT was non-inferior to PE-IP in terms of reducing PTSD scores at post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 64 publications
12
128
0
Order By: Relevance
“…Post-intervention PCL scores yielded an average of 46.27 ( SD = 19.39; ranged from 17–85). For more description of the sample, please refer to the principal study by Acierno and colleagues (2017). Of the sample, 91% of the participants (N=136) positively endorsed sleep problems (Yes or No) for Criterion D of the PTSD DSM I diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Post-intervention PCL scores yielded an average of 46.27 ( SD = 19.39; ranged from 17–85). For more description of the sample, please refer to the principal study by Acierno and colleagues (2017). Of the sample, 91% of the participants (N=136) positively endorsed sleep problems (Yes or No) for Criterion D of the PTSD DSM I diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Therapists met weekly with a senior-level PE trainer/therapist for supervision throughout the duration of the study. Treatment fidelity was maintained at or above 90% across and within conditions, assessed through random sampling of 20% of therapy session audiotapes rated according to session-specific procedures directly corresponding to the PE treatment manual (Acierno et al, 2017). Each therapist was randomly assigned to provide treatment to participants in both the in-person and telehealth conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Telehealth has been developed and shown to be effective broadly (Backhaus et al, 2012). It has also been demonstrated that its effects can be equivalent to those of face-to-face therapy in specific areas of mental health, such as post-traumatic stress disorder (Acierno et al, 2016(Acierno et al, , 2017Morland et al, 2014Morland et al, , 2015Yuen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%